PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BEI - Mochammad Karim Amrulloh; Dwi Ermayanti Susilo (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
This study aims to analyze the effect of company growth and structure on profitability in state-owned banks listed on the Indonesia Stock Exchange. The research uses quantitative research methods which are carried out through data collection with secondary data, namely the Financial Statements of State-Owned Banks Listed on the Indonesia Stock Exchange for the period 2012-2021. The sample in this study is in the form of balance sheets and profit/loss reports for state-owned banks listed on the Indonesia Stock Exchange for the period 2012-2021, data analysis using multiple linear regression statistical methods and hypothesis testing. The results show that 1) There is a value of the influence of company growth on profitability in BUMN Banking Listed on the Indonesia Stock Exchange with t of 2.765 with t table of 2.02 (t count > t table), the significance value obtained is 0.016 < 0.05 2 ) There is no effect of capital structure on profitability in BUMN banking listed on the Indonesia Stock Exchange, with a t value of 17.344 with a t table of 2.02 (t count < t table), the significance value obtained is 0.000 < 0.05